2021
DOI: 10.1016/j.jechem.2020.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Highly active Pd containing EMT zeolite catalyst for indirect oxidative carbonylation of methanol to dimethyl carbonate

Abstract: An efficient catalytic system for the synthesis of glycerol carbonate by oxidative carbonylation of glycerol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 70 publications
(95 reference statements)
4
20
0
Order By: Relevance
“…The TEM images of fresh and used Pd/NaY-60 catalysts indicated that the large Pd nanoparticles were formed because of the catalytic test. This was in line with the previous observation revealing the palladium sintering on the Pd/NaY catalyst after the catalytic test [41]. The used Pd/NaY-150 catalyst contained Pd nanoparticles of 6.3 nm that were remarkably smaller than the counterparts on the Pd/NaY-60 catalyst (Fig.…”
Section: Understanding the Formation Of Mechanical Pressure-mediated Active Sites Insupporting
confidence: 92%
See 2 more Smart Citations
“…The TEM images of fresh and used Pd/NaY-60 catalysts indicated that the large Pd nanoparticles were formed because of the catalytic test. This was in line with the previous observation revealing the palladium sintering on the Pd/NaY catalyst after the catalytic test [41]. The used Pd/NaY-150 catalyst contained Pd nanoparticles of 6.3 nm that were remarkably smaller than the counterparts on the Pd/NaY-60 catalyst (Fig.…”
Section: Understanding the Formation Of Mechanical Pressure-mediated Active Sites Insupporting
confidence: 92%
“…As described previously, the Pd/NaY catalyst was prepared by an ion-exchange method with Pd precursor of Pd(NH 3 ) 4 2+ ; and the low-temperature calcination at 200 ºC caused the Pd(NH 3 ) 4 2+ to lose partially the NH 3 ligands and to generate the Pd(NH 3 ) n 2+ (n  2) sites on the catalyst [41]. Neither Pd clusters (below 2 nm) nor nanoparticles were observed on the fresh Pd/NaY-60 catalyst before the catalytic test (Fig.…”
Section: Understanding the Formation Of Mechanical Pressure-mediated Active Sites Inmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, DMC is also widely used as a fuel oil additive due to its high oxygen content (53 %) [4] and employed as a key solvent in the synthesis of commodity polymers [5] . There are several routes for producing DMC, such as the oxidative carbonylation of methanol, [6] direct synthesis from CO 2 and methanol, [7,8] methanolysis of urea, [9] and transesterification of cyclic carbonate (propylene carbonate or ethylene carbonate) with methanol [10,11] . Therefore, DMC synthesis via the transesterification of propylene carbonate (PC) with methanol under mild conditions is a clean catalytic route eliminating the use of toxic and corrosive reagents and is recognized as a promising and environmentally benign route for DMC.…”
Section: Introductionmentioning
confidence: 99%
“…The DRIFTS spectra of pyridine absorbed on samples MoVBiO‐M‐120, MoVBiO‐N‐120, MoVBiO‐T‐120 and MoVBiO‐T‐175 are presented in Figure 10. The weak band at 1446 cm −1 is assigned to the Lewis‐bound pyridine [58] . The band at 1537 cm −1 corresponds to Brønsted‐bound pyridine, and the band at 1487 cm −1 is assigned to pyridine associated with both Lewis and Brønsted acid sites [58] .…”
Section: Resultsmentioning
confidence: 99%